Dampak E-Service Quality terhadap Customer Satisfaction dan Customer Loyality Website Blibli - Fadli, Muhammad; Monalisa, Siti; Muttakin, Fitriani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Blibli.com is one of the most popular web-based e-commerce in Indonesia that continues to provide the best service to create customer satisfaction and lead them to make repeat purchases. The relationship between e-service quality to customer satisfaction and customer loyalty on the Blibli.com website needs to be measured to determine its effect, so this is the background of this research. This research uses quantitative methods with nonprobability sampling techniques and purposive sampling for sample collection. Data were collected through questionnaires from 100 respondents who use Blibli.com in the UIN SUSKA RIAU environment. Data analysis was carried out using Structural Equation Modeling (SEM) and SMARTPLS 4 software. The results showed that customer satisfaction has a significant influence on customer loyalty with a path coefficient value of 0.414, a P-value of 0.003, and a T value of 2.952 (> 1.96). In addition, e-service quality also has a significant influence on customer loyalty with a path coefficient value of 0.462, a P-value of 0.001, and a T value of 3.362 (> 1.96).